Traditional Culinary Marketing Communication Strategies in the Face of Foreign Culinary Trends: (Case Study of Haji Mahmud Chicken Noodles) - Zahra Zanzabilla Nasution; Zuhriah Zuhriah (Badan Penerbit STIEPARI Press, 2025)
This study explores the marketing communication strategies employed by traditional culinary entrepreneurs in response to the growing dominance of global food trends. The focus of the research is a case study of Mie Ayam Jamur Haji Mahmud Medan. Utilizing a qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation. The findings reveal that the business implements marketing communication strategies through social media-based promotion, cultural narratives, and the strengthening of local identity. These strategies not only sustain the existence of cuisine but also add value through cultural storytelling and menu adaptation without compromising the original identity. The study emphasizes the importance of educational and persuasive communication in attracting consumers influenced by global trends. These findings contribute to a deeper understanding of how local culinary MSMEs can compete strategically amid the wave of gastronomic globalization, and highlight the significance of innovation in preserving Indonesia's traditional culinary heritage.